PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andriana, Denny (Program Studi Akuntansi FPEB UPI, 2013)
This study aims to examine the characteristics of the company, such as leverage and profitability, and its influence on disclosure of social responsibility of mining companies listed in Indonesia Stock Exchange (BEI). Corporate social responsibility disclosure indicators refer to Global Reporting Initiatives (GRI) 2000 guidelines.Observations made on 30 mining companies listed on the BEI for the period 2009-2011 refers to the purposive sampling method undertaken in this study, resulting in 13 companies being the study sample. Data analysis technique used in this research is doubled linear regression.The test results proved that leverage has a negative effect but failed to show significant influence on corporate social responsibility disclosure. Variable profitability on the other hand successfully proves positive influence on disclosure of corporate social responsibility but the influence is not significant